Identifikasi Cemaran Bakteri Escherichia Coli Pada Jamu Gendong Yang Diperjualbelikan Disekitar Jalan Abdul Kadir Kota Makassar - Dita Ellyana Artha (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2017)
Research has been done. Jamu carrying is one of the traditional medicine that is highly observed by the community because the price is cheap and easy to obtain. To find out whether or not Escheichia coli bacteria in herbal carrying in the herbalist sellers carry around Abdul Kadir street. This research was conducted by laboratory observation method which presented in the form of deskritif. Performed by purposive sampling. From the observed results, samples B and C Jamu carrying contain Escherichia coli and sample A did not contain Escherichia coli.Conclusion of three samples studied two of which contain Escherichia coli bacteria. Disasrankan to the next researcher to check the contamination of the herbal carrying quantitatively by calculating the total plate number.